2011
DOI: 10.1136/thoraxjnl-2011-200169
|View full text |Cite
|
Sign up to set email alerts
|

A 37-year observation of mortality in Chinese chrysotile asbestos workers

Abstract: Objectives This 37-year prospective cohort study was undertaken to provide additional evidence for mortality risks associated with exposure to chrysotile asbestos. Methods 577 asbestos workers and 435 control workers in original cohorts were followed from 1972 to 2008, achieving a follow-up rate of 99% and 73%, respectively. Morality rates were determined based on person-years of observation. Cox proportional hazard models were constructed to estimate HRs of causespecific mortality, while taking into account a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 15 publications
1
51
0
Order By: Relevance
“…The significant association of the duration of occupational exposure to asbestos with all-cause mortality and benign lung disease mortality, respectively, underline the validity of our findings. Although we did not observe a statistically significant association between occupational exposure to asbestos and mortality from all cancers or lung cancer, in particular we observed positive non-significant trends that were in line with previous findings [9,15,21,23]. A borderline significant association of the duration of occupational exposure to asbestos with lung cancer mortality may support the assumption of causality between exposure to asbestos dust and lung cancer.…”
Section: The Role Of Smokingsupporting
confidence: 80%
See 1 more Smart Citation
“…The significant association of the duration of occupational exposure to asbestos with all-cause mortality and benign lung disease mortality, respectively, underline the validity of our findings. Although we did not observe a statistically significant association between occupational exposure to asbestos and mortality from all cancers or lung cancer, in particular we observed positive non-significant trends that were in line with previous findings [9,15,21,23]. A borderline significant association of the duration of occupational exposure to asbestos with lung cancer mortality may support the assumption of causality between exposure to asbestos dust and lung cancer.…”
Section: The Role Of Smokingsupporting
confidence: 80%
“…All-cause mortality and respiratory mortality As in SHIP, significantly increased risks for all-cause mortality [6,9,20,21] and benign lung disease mortality [7,22,23] had previously been observed. The significant association of the duration of occupational exposure to asbestos with all-cause mortality and benign lung disease mortality, respectively, underline the validity of our findings.…”
Section: The Role Of Smokingmentioning
confidence: 99%
“…15 Although some studies have suggested that chrysotile is less harmful compared with amphiboles, 14 there is robust evidence showing an excess mortality risk because of lung cancer, all cancers, and nonmalignant respiratory diseases in chrysotile-exposed workers, even for those exposed to low concentrations. 16 Asbestos-containing brake pads, brake linings, and brake blocks are still commercialized in Colombia. Brake linings are used for both passenger and heavy vehicles (i.e., with important differences in size and thickness), whereas brake blocks are exclusively used for heavy vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…clearly attributable to chrysotile exposure in Chinese studies than in mostly of the western studies with a prevalence of male smoker cohorts [5] (p. 250) and [30].…”
mentioning
confidence: 99%